Building Eminence through Evidence - Horgan, Denis (Biomed Hub, 2017)
With modern-day medicine going the way it is - new developments, great science, the advent of personalised medicine and more - there's little doubt that healthcare can move in the right direction if everything is put in place to allow it to do so. But in many areas progress is being halted. Or at the very least slowed. Like it or not, many front-line healthcare professionals still do things the way they did things three decades ago, and are reluctant to adapt to new methods (assuming they are aware of them). Evidence exists that today's rapidly developing new medicines and treatments can positively influence healthcare in modern-day Europe, but a gap in education (also applying to patients and politicians), often exacerbated by “fake news” on the internet, is hampering uptake of new and often better methods, while even causing doubts about vaccines. More understanding at every level will inevitably lead to swifter integration of innovation into the healthcare systems of Europe. The time to look, listen and learn has come.